ANALISIS SEBERAPA BESAR PENGARUH INFORMASI TEKNOLOGI DALAM PENGAMBILAN KEPUTUSAN SUATU ORGANISASI - Adris Triseptina; Muhammad Irwan Padli Nasution (Kohesi: Jurnal Sains dan Teknologi, 2025)
The purpose of this research is to analyze the impact of information technology (IT) on the effectiveness of decision making in organizations. In modern organizations, IT plays a critical role in presenting accurate and relevant data, enabling management to make data-driven decisions more quickly. This research uses a quantitative approach using a survey method using a questionnaire as a data collection tool. Respondents to this study were employees selected randomly to provide a comprehensive understanding of the role of IT in the decision-making process. The research results show that there is a positive and significant influence between the use of IT on decision effectiveness. Regression analysis produces an equation (Y = 8.332 + 0.592X), which shows that every 1% increase in IT use can increase decision effectiveness by 59.2%. Furthermore, the results of the linearity and normality tests also prove that the data used is normally distributed and there is a linear relationship between IT variables and decision making. In summary, this research confirms that optimizing the use of IT in organizations can improve the quality of decision making and ultimately contribute to achieving organizational goals. This research shows that it is important for businesses to invest in reliable IT infrastructure to support more effective management processes. KEYWORDS: Information Technology, Decision Making, organization